Decoding immune cell interactions during cardiac allograft vasculopathy: insights derived from bioinformatic strategies - Thorp, Edward B.; Ananthakrishnan, Aparnaa; Lantz, Connor W. (Frontiers in Cardiovascular Medicine, 2025)
Chronic allograft vasculopathy (CAV) is a major cause of late graft failure in heart transplant recipients, characterized by progressive intimal thickening and diffuse narrowing of the coronary arteries. Unlike atherosclerosis, CAV exhibits a distinct cellular composition and lesion distribution, yet its pathogenesis remains incompletely understood. A major challenge in CAV research has been the limited application of advanced “-omics” technologies, which have revolutionized the study of other vascular diseases. Recent advancements in single-cell and spatial transcriptomics, proteomics, and metabolomics have begun to uncover the complex immune-endothelial-stromal interactions driving CAV progression. Notably, single-cell RNA sequencing has identified previously unrecognized immune cell populations and signaling pathways implicated in endothelial injury and vascular remodeling after heart transplantation. Despite these breakthroughs, studies applying these technologies to CAV remain sparse, limiting the translation of these insights into clinical practice. This review aims to bridge this gap by summarizing recent findings from single-cell and multi-omic approaches, highlighting key discoveries, and discussing their implications for understanding CAV pathogenesis.